A percepção dos docentes da Faculdade de Direito da Universidade Federal do Ceará sobre a lei nº 13.709/2018 (LGPD) na gestão da educação superior. - Viana, Marcelo Muniz Baptista (2024)
The Federal University of Ceará (UFC) faces the challenge of adapting higher education management to the General Data Protection Law (LGPD), ensuring the security and privacy of personal data. Compliance with the LGPD strengthens transparency and trust within the academic community. Collecting and using data is fundamental for planning and decision- making, but requires responsibility and respect for privacy. Implementing the LGPD at UFC requires understanding the specific challenges, such as the lack of knowledge on the part of teachers and the lack of technological infrastructure. The objectives outlined will be to analyze the challenges and perspectives of the LGPD in the management of higher education, based on the perception of professors at the UFC Law School. The methodology used will be descriptive and exploratory, using semi-structured interviews with professors from the UFC Law course. Regarding the expected results, the research presented in this summary contributes to the understanding of the challenges and perspectives of the LGPD for the management of higher education, providing support for the formulation of public policies and for the promotion of a data protection culture in educational institutions. In conclusion, implementing the LGPD in higher education institutions is a complex and challenging process that requires a joint effort from the academic community.